2010
DOI: 10.1074/jbc.m109.091710
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response to Iron Deficiency in Saccharomyces cerevisiae

Abstract: Iron is an essential cofactor for enzymes involved in numerous cellular processes, yet little is known about the impact of iron deficiency on cellular metabolism or iron proteins. Previous studies have focused on changes in transcript and proteins levels in iron-deficient cells, yet these changes may not reflect changes in transport activity or flux through a metabolic pathway. We analyzed the metabolomes and transcriptomes of yeast grown in iron-rich and iron-poor media to determine which biosynthetic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
163
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(200 citation statements)
references
References 49 publications
(60 reference statements)
25
163
0
1
Order By: Relevance
“…Moreover, seven up-regulated genes were associated with the pyruvate metabolic process. Interestingly, pyruvate production and increased glycolysis has also been observed during iron deprivation in S. cerevisiae (68). Our microarray data also revealed several transcriptional regulator genes that showed Cap2 dependence, of which 25 genes were up-regulated, and 15 were down-regulated.…”
Section: Albicans Cap2 Is a Hap4l-bzip Bipartite Domain Protein-mentioning
confidence: 62%
“…Moreover, seven up-regulated genes were associated with the pyruvate metabolic process. Interestingly, pyruvate production and increased glycolysis has also been observed during iron deprivation in S. cerevisiae (68). Our microarray data also revealed several transcriptional regulator genes that showed Cap2 dependence, of which 25 genes were up-regulated, and 15 were down-regulated.…”
Section: Albicans Cap2 Is a Hap4l-bzip Bipartite Domain Protein-mentioning
confidence: 62%
“…We made significant attempts to increase the iron content within the enzyme, including reduction of the zinc content in the expression media, stripping out zinc with subsequent addition of iron during purification, and manipulation of the yeast expression conditions to favor iron incorporation over zinc (42). Although these attempts led to the production of highly purified enzyme with iron incorporated at the dimetal center up to ϳ50%, we were unsuccessful at achieving 100% replacement with iron.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ford et al (34) found in a cross-sectional study of 8296 adults who participated in the National Health and Nutrition Examination Survey (NHANES) that iron deficiency tends to increase HbA1c level rather than decreasing it. In addition, Shakoury-Elizeh et al (35) showed that iron deficiency leads to impairment in glucose metabolism by altering glucose storage.…”
Section: Discussionmentioning
confidence: 99%